Fenomena Serang Simbolik dalam Debat Publik di Pemilihan Umum 2024: The Phenomenon of Symbolic Attacks in Public Debates in 2024 Election - Arifin, Muhammad Risal (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2025)
The campaign stage in the implementation of the election is one of the important stages for election participants. This campaign stage conveys the vision, mission, and flagship programs of each presidential and vice-presidential candidate, one of which is presented through a public debate. The use of various political communication strategies in the campaign will be carried out by each candidate to gain support from the wider community, including a negative campaign approach. This research is qualitative research with a literature study approach. This research highlights the phenomenon of symbolic attacks in implementing the 3rd Public Debate, the 2024 election. This phenomenon is one of the political communication strategies in the campaign, to reduce the credibility of the candidate being attacked, thereby reducing public trust in the candidate. This study looks at the low level of public satisfaction with presidential candidate number 2 from his appearance in the third public debate. The low level of public satisfaction with presidential candidate number 2 is a sign that the symbolic attacks carried out by presidential candidates’ number 1 and 3 in the public debate are not just criticism of the performance of presidential candidate number 2, but also show the success of the symbolic attacks in influencing public perception. Meanwhile, this symbolic attack phenomenon can also cause prolonged polarization in society or between supporters, which ultimately affects community life in the social environment.